NILAI-NILAI BUDAYA DALAM NOVEL PADA SENJA YANG MEMBAWAMU PERGI KARYA BOY CANDRA - Intan Sri Kemuning; Syafrial Syafrial; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled Nilai-Nilai Budaya dalam Novel Pada Senja yang Membawamu Pergi by Boy Candra. The aim of this study is to describe the cultural value in novel Pada Senja yang Membawamu Pergi by Boy Candra. The types of this research is qualitative descriptive research that trying to solve the problem based on existing data. Based on this research was found 70 data of cultural value, (a) human and loves 12 data, (b) human and beauty 10 data, (c) human and pain 15 data, (d) human and justice 2 data, (e) human and a view of life, (f) human and responsibility and devotion 11 data, (g) human and nerves 13 data, (h) human and hope 10 data.Keyword: Cultural value, novel Pada Senja yang Membawamu Pergi